Intelligent computing theories and application : 15th International Conference, ICIC 2019, Nanchang, China, August 3-6, 2019 : proceedings.: 15th International Conference, ICIC 2019, Nanchang, China, August 3-6, 2019 : proceedings. Part I ([2019]) - Unknown
No abstract available